Mn2+ and Mn4+ competition in photoluminescence and persistent luminescence - Hei-Yui Kai; Ka-Leung Wong; Peter A. Tanner (Next Materials)
M2La3Sb3O14 (M = Mg, Zn, Mn) exhibit ordered, and for Ca, disordered, rhombohedral pyrochlore systems. The photoluminescence (PL) and persistent luminescence (PersL) has been studied for the Mn-doped Mg, Zn and Ca systems in addition to M = Mn, with major focus upon the Mg system. The systems exhibit differences in the Mn2+ and Mn4+ PL, and also in the PersL. In addition to bandgap excitation, the PersL of Mn2+ is due to metal-to-metal charge transfer (MMCT) rather than tunneling. The thermally stimulated luminescence (TL) and PersL decay kinetics have been fitted to give kinetics order and activation energies. The shallowest trap for M = Mg (Zn) has the activation energy of 0.42 eV (0.71 eV) and obeys second order kinetics. TL and temperature-stop (TSTOP) data can explain the anomalous temperature quenching of Mn2+ PL, whereas the Mn4+ PL follows a single barrier model. Using the determined vacuum referred binding energy (VRBE) data, the PersL results for M = Mg have been rationalized. The unusual properties enable a novel anti-counterfeiting material device to be constructed. Our results are especially relevant for Physical, Inorganic and Materials Chemists to understand and tune PL and PersL properties of solid state systems. It is found that disorder is not a criterion for improvement of PersL.